Anti-Melanogenic Activity of Different Extracts from Aerial Parts of Nepeta glomerulosa on Murine Melanoma B16F10 Cells: Anti-Melanogenic Activity of Nepeta glomeruloas on Murine Melanoma B16F10 Cells - Seyed Ahmad Emami; Mohammad Sadeghi; Rezvan Yazdian-Robati; Atefeh Arab; Zahra Tayarani-Najaran (Iranian Journal of Pharmaceutical Sciences, 2017)
Nepeta glomerulosa Boiss. is a medicinal plant used in traditional medicine. The aim of this study was to evaluate the anti-melanogenesis inhibitory activity of Methanol (MeOH), n-hexane, acetate (EtAc), dichloromethane (CH2Cl2), n-butanol (BuOH), and H2O extracts isolated from N. glomerulosa in B16 melanoma cell line. The B16F10 cell line viability after treatment with increasing concentrations of different extracts of the plant (50-200 μg/ml) was measured by using MTT. The inhibitory effect on synthesis of melanin, mushroom tyrosinase activity, cellular tyrosinase, and effect on oxidative stress was determined by the colorimetric and fluorometric method. The data showed that at concentrations <200 μg/ml, all extracts did not show significant toxicity on melanoma cells. The amount of melanin synthesis by MeOH and CH2Cl2 extracts and mushroom tyrosinase activity by the MeOH extract declined in B16F10 cells. In addition to the capacity of MeOH, n-hexane and CH2Cl2 extracts in decreasing the amount of reactive oxygen species (ROS) in melanoma cells all extracts revealed the remarkable antioxidant activity. Our results showed the melanogenesis inhibitory and antioxidant effects of N. glomerulosa on B16F10 cells may recommend a novel agent in diminishing skin pigmentation and skin aging in cosmetic industry.